A Artikel: IMPLEMENTASI NILAI KARAKTER DALAM PEMBELAJARAN PJOK DITINJAU DARI KURIKULUM MERDEKA DI SMPN SE-KECAMATAN GOLEWA - Bate, Nikodemus (STKIP CITRA BAKTI, 2024)
This study is qualitative descriptive research. The purpose of this research is to identify how character values are applied in the teaching and learning process of Physical Education, Sports, and Health (PJOK) at the public junior high school level (SMPN) within the context of the Kurikulum Merdeka (Independent Curriculum) and how the newly implemented curriculum supports this integration. Data were collected through interviews, observations, and document analysis. The findings show that character values such as discipline, responsibility, cooperation, and honesty can be effectively integrated into PJOK learning through varied and innovative teaching strategies aligned with the principles of the Kurikulum Merdeka.